Managing Infrastructure in the Stream Environment. (13th October 2018) - Sholtes, Joel S.; Ubing, Caroline; Randle, Timothy J.; Fripp, Jon; Cenderelli, Daniel; Baird, Drew C.
Abstract: Riverine infrastructure provides essential services for the operation and development of the world's nations and their economies. When much of this infrastructure was built in the United States, fluvial processes and stream ecology were not well understood, putting it in conflict with and at risk from the stream environment. High maintenance costs are often required to keep such infrastructure viable and some of it has led to the degradation of aquatic and riparian ecosystems. This commentary paper lays the foundation for infrastructure designers and managers to build and manage infrastructure in a manner both resilient to riverine hazards and more compatible with aquatic and riparian ecosystem needs. We introduce fundamental fluvial geomorphic and ecosystem concepts and provide a decision‐making framework to replace or repair existing infrastructure or build new infrastructure. Common management challenges associated with 11 riverine infrastructure types are discussed and we provide suggestions on how each infrastructure type can be better built and managed within stream corridors. We close with a discussion on managing infrastructure under future hydrologic uncertainty and in response to natural disasters. Abstract : Research Impact Statement : We present a framework for infrastructure designers and managers to build and manage riverine infrastructure in a manner that is both resilient to hazards and more compatible with stream ecosystems.